Poverty and social exclusion in the UK. - Bramley, Glen; Bailey, Nick (Professor of urban studies) (Policy Press, 2018)
"How many people live in poverty in the UK, and how has this changed over recent decades? Are those in poverty more likely to suffer other forms of disadvantage or social exclusion? Is exclusion multi-dimensional, taking different forms for different groups or places? Based on the largest UK study of its kind ever commissioned, this fascinating book provides the most detailed national picture of these problems. Chapters consider a range of dimensions of disadvantage as well as poverty -- access to local services or employment, social relations or civic participation, health and well-being. The book also explores relationships between these in the first truly multi-dimensional analysis of exclusion. Written by leading academics, this is an authoritative account of welfare outcomes achieved across the UK. A companion volume Poverty and Social Exclusion in the UK: Volume 1 focuses on specific groups such as children or older people, and different geographical areas."--